A Critical Study on Components of Political Thought in Amir Adel tale by Nizam al-Mulk - Forouzani, Seyed Aboulghasem; Pirouzan, Hadi (Journal of History Culture and Art Research, 2017)
Making historiography about Iran’s political thought in Seljuk era is futile without considering Nizam al-Mulk’s Siyasatnama. Applying historical approach to several tales in this book, Nizam al-Mulk endeavored to formulate his favorite and pleasant political-religious thought which defines political thought of Sunni Islam. The first and the most prominent and detailed tale is Amir Adel, which is investigated closely in this research by comparing to the other historical texts. This study sheds light on differences and peculiar aspects of Nizam al-Mulk’s Amir Adel narration and seeks reasons behind these significant differences in Nizam al-Mulk’s religious and political thought. Hence, there are two questions for this research: 1- What are the components of Nizam al-Mulk’s political thought; 2- How these components can form his Amir Adel narration.